Proposta de construção de matrizes insumoproduto para o Estado do Ceará: uma análise comparativa das alterações nas relações intersetoriais do Estado antes e após os eventos socioeconômicos ocorridos no ano de 2020 - Freitas, Pedro Thales Lima (2024)
This study aims to construct input output matrices (IOM) for the State of Ceará, analyzing the changes in intersectoral relationships before and after the socioeconomic events that occurred in 2020, particularly the COVID 19 pandemic. Utilizing databases from the Ceará State Department of Finance, including the Electronic Invoice (NFe) and the Electronic Tax Receipt (CFe), IOMs were estimated for the years 2019 and 2022. The methodology employed followed the basic Input Output theory, adapted to the regional context. The comparative analysis for the mentioned years revealed some changes in the state's economic dynamics: in both periods, although a small number of sectors continued to hold almost the entire ty of production, import, and export values, changes were observed in the most relevant sectors of some scenarios, along with greater diversification in the scope of exports. Furthermore, the construction of IOMs highlighted the impact of the COVID 19 pand emic on Ceará's economy, as all general sectors analyzed showed a decline in nominal added value in 2022. In terms of absolute total production numbers, the results vary depending on the sector analyzed. This study contributes to the understanding of regional economic dynamics, the assessment of alternative development and economic growth strategies, and the development of effective fiscal and tax public policies.